Decoherence of phonons in weakly and strongly-interacting Bose-Einstein condensates - Howl, R. (2016)
This work investigates the theoretical and experimental decoherence of phonons in weakly and strongly-interacting Bose-Einstein Condensates (BECs). The theoretical analysis treats phonons as open quantum systems where the environment comprises all other quasi-particle modes of the BEC. The phonons are assumed to be Gaussian states and the time in which they decohere is estimated from the evolution of their purity and nonclassical depth in the dissipative channel. The calculations are performed for various BEC systems and it is found that the excited phonon states will always decohere much more rapidly than the rate at which they relax back to equilibrium with the environment.